Study on Fungal Flora in the Midgut of the Larva and Adult of the Different Populations of the Malaria Vector Anopheles stephensi - L Tajedin; J Hashemi; MR Abaei; L Hosseinpour; F Rafei; HR Basseri (Tehran University of Medical Sciences, 2009)
Background: Many microorganisms in midgut of mosquito challenge with their host and also other pathogens present in midgut. The aim of this study was presence of non-pathogens microorganisms like fungal flora which may be crucial on interaction between vectors and pathogens. }Methods: Different populations of Anopheles stephensi were reared in insectary and objected to determine fungal flora in their midguts. The midgut paunch of mosquito adults and larvae as well as breading water and larval food samples transferred on Subaru-dextrose agar, in order to detect the environment fungus. Results: Although four fungi, Aspergillus, Rhizopus, Geotrichum and Sacharomyces were found in the food and water, but only Aspiragilus observed in the midgut of larvae. No fungus was found in the midgut of adults. This is the first report on fungal flora in the midgut of the adults and larvae of An. stephensi and possible stadial transmission of fungi from immature stages to adults. Conclusion: The midgut environment of adults is not compatible for survivorship of fungi but the larval midgut may contain few fungi as a host or even pathogen.